2015
DOI: 10.1200/jco.2014.58.3302
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib Therapy for Advanced Lung Adenocarcinoma and a ROS1 Rearrangement: Results From the EUROS1 Cohort

Abstract: Crizotinib was highly active at treating lung cancer in patients with a ROS1 rearrangement, suggesting that patients with lung adenocarcinomas should be tested for ROS1. Prospective clinical trials with crizotinib and other ROS1 inhibitors are ongoing or planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
246
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(288 citation statements)
references
References 46 publications
21
246
3
8
Order By: Relevance
“…This recommendation is evidence based and supported by 9 studies, 30e38 6 of which informed on the association between ROS1 rearrangement and patient or tumor characteristics 30,31,34e37 and consisted of 1 prospective cohort study (PCS), 35 1 prospective-retrospective cohort study (PRCS), 31 and 4 retrospective cohort studies (RCSs). 30,34,36,37 The 3 remaining studies assessed clinical outcomes of patients treated with the ROS1-targeted therapy crizotinib 32,33,38 and included 1 nonrandomized clinical trial 33 and 3 RCSs. 32,38 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 6).…”
Section: Strong Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…This recommendation is evidence based and supported by 9 studies, 30e38 6 of which informed on the association between ROS1 rearrangement and patient or tumor characteristics 30,31,34e37 and consisted of 1 prospective cohort study (PCS), 35 1 prospective-retrospective cohort study (PRCS), 31 and 4 retrospective cohort studies (RCSs). 30,34,36,37 The 3 remaining studies assessed clinical outcomes of patients treated with the ROS1-targeted therapy crizotinib 32,33,38 and included 1 nonrandomized clinical trial 33 and 3 RCSs. 32,38 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 6).…”
Section: Strong Recommendationmentioning
confidence: 99%
“…30,34,36,37 The 3 remaining studies assessed clinical outcomes of patients treated with the ROS1-targeted therapy crizotinib 32,33,38 and included 1 nonrandomized clinical trial 33 and 3 RCSs. 32,38 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 6). Refer to SDC Table 7 for a summary of findings from studies supporting the use of ROS1 molecular or cytogenetic testing to enable selection of patients for ROS1-targeted therapy.…”
Section: Strong Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high degree of homology between the kinase domains of ROS1 and ALK, and the potent inhibition of ROS1 kinase by crizotinib, the results were excellent and confirmed in the final report in 2014 [17]. This trial had an immediate impact on clinical practice, as demonstrated by the EUROS1 cohort study [18]. The ongoing EUCROSS trial is expected to produce further relevant data (NCT02183870), while other studies are focusing on acquired resistance and other ROS1 inhibitors to overcome crizotinib resistance [19].…”
mentioning
confidence: 67%
“…Patients with ROS proto-oncogene 1 RTK (ROS1) rearranged NSCLC in general respond to treatment with the ROS1 inhibitor-crizotinib very well with quite durable remissions being the norm, however these tumors eventually become resistant as well (76,77). There is limited data available on the mechanisms of acquired resistance to crizotinib in ROS1 positive NSCLC, however several secondary ROS1 mutations that can cause resistance have been identified, for example the G2026M mutation (gatekeeper) or the L2155S solvent-front (D2033N) mutation which can still respond to the multi-targeted TKI, cabozantinib which has ROS inhibitory activity as well (78)(79)(80).…”
Section: Rosmentioning
confidence: 99%